2021
DOI: 10.1016/j.heliyon.2021.e07790
|View full text |Cite
|
Sign up to set email alerts
|

Influence of location, elevation gradients, processing methods, and soil quality on the physical and cup quality of coffee in the Kafa Biosphere Reserve of SW Ethiopia

Abstract: In-depth forest coffee cup quality assessments have not been conducted yet on Kafa Biosphere Reserve coffees. Hence, the influence of location, elevation gradient, and processing methods on coffee bean physical and sensorial qualities, and the relationship between soil and coffee quality variables were studied in 2017. Districts (Gimbo, Gawata, and Decha), elevation gradient ranges (low-<1600, mid-1600-1800, and high->1800 m a.s.l), and processing methods (wet, semi-wet, and dry) were taken as factors. Prelimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
3
17
0
3
Order By: Relevance
“…e coffees are grown on clayey soils and soils that have a high molybdenum content. As reported by Tassew et al [42] and Abebe et al [41], the positive influence of fine-textured soils was observed on the cup quality of Ethiopian coffee. Furthermore, the coffees have a relatively high bean moisture content that is directly related to increased soil potassium, calcium, magnesium, sodium, organic carbon content, and high soil pH.…”
Section: Discussionsupporting
confidence: 62%
“…e coffees are grown on clayey soils and soils that have a high molybdenum content. As reported by Tassew et al [42] and Abebe et al [41], the positive influence of fine-textured soils was observed on the cup quality of Ethiopian coffee. Furthermore, the coffees have a relatively high bean moisture content that is directly related to increased soil potassium, calcium, magnesium, sodium, organic carbon content, and high soil pH.…”
Section: Discussionsupporting
confidence: 62%
“…Handpicked cherry beans are important to get a better coffee's quality. However, maintaining the quality of coffee depends on the suitable processing method [5]. The differences of coffee characteristics such as aroma, flavor, and experiences is resulted by different processes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, these findings suggest that the drift of these compounds under changing temperatures might be predominantly genotype-related. In a more recent study also performed in Ethiopia, C. arabica grown under diverse forests covers and densities (Tassew et al, 2021), also reported that cup quality organoleptic attributes (acidity, body, raw total, flavor, and cup total values) as well as grade were significantly and positively affected by shade and increasing elevation.…”
Section: Shade Effects On Organoleptic Attributesmentioning
confidence: 87%